2018
DOI: 10.1021/acs.jchemed.8b00212
|View full text |Cite
|
Sign up to set email alerts
|

Social and Tactile Mixed Reality Increases Student Engagement in Undergraduate Lab Activities

Abstract: Undergraduate lab sessions play a crucial role in building and reinforcing conceptual understanding in STEM education. In third and fourth year higher education, lab sessions can be challenging to incorporate into the curriculum due to cost, safety, or difficulty in realizing abstract concepts. Mixed reality (MR) systems provide a novel solution due to their ability to nurture collaboration and tactile interaction. In this work, an MR system designed for use in chemical kinetics undergraduate curriculum is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
(34 reference statements)
0
26
0
1
Order By: Relevance
“…These models can aid in creating experiences that are learner-centered, interactive and support the mastery of content knowledge. Augmented reality (AR) is among those emerging technologies that show significant potential for education (Barrett et al 2018;Birt and Cowling 2017;Cheng and Tsai 2013;Godwin-Jones 2016;Liu and Tsai 2013;Quint, Sebastian, and Gorecky 2015;Wang 2017). AR can be defined as 'a means with which to supplement the real world with digital information through a visual interface' (Richey 2018, p. 11).…”
Section: Introductionmentioning
confidence: 99%
“…These models can aid in creating experiences that are learner-centered, interactive and support the mastery of content knowledge. Augmented reality (AR) is among those emerging technologies that show significant potential for education (Barrett et al 2018;Birt and Cowling 2017;Cheng and Tsai 2013;Godwin-Jones 2016;Liu and Tsai 2013;Quint, Sebastian, and Gorecky 2015;Wang 2017). AR can be defined as 'a means with which to supplement the real world with digital information through a visual interface' (Richey 2018, p. 11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that AR technology may enhance educational outcomes [18] and students' practical laboratory skills in higher education [17,22]. AR has been used successfully to engage students in scientific thinking, including argumentation, by pushing students to develop and argue scientific explanations in gamified learning environments [8].…”
Section: Ar Assisted Learning Of Laboratory Skills In Higher Educationmentioning
confidence: 99%
“…These simplifications are reasonable for the scope of this study and imply the generated equations. Here we rely on the models published in the literature [2]. A brief description of the model-equations are as follows:…”
Section: The Process Modelmentioning
confidence: 99%
“…In addition to these efforts, improved distillation operation [29] as well as new configurations and systems have also been invented for specific applications [14] with improved performance in terms of separation and/or energy consumption [8,10]. The ethanol-water mixture is trivial, but still an excellent candidate for the analysis of binary distillation for multiple reasons: (a) it is a good example of a nonideal, azeotrope-forming mixture; (b) has minimal human toxicity and environmental impact; (c) not corrosive nor chemically aggressive; (d) relatively economical and available in large quantity [2]. In addition, the ethanol-water mixture is separated by distillation in numerous industries, from biorefineries [12] to ethanol [9] and alcoholic beverage production.…”
Section: Introductionmentioning
confidence: 99%